(untitled) (INNOVATIVE ECONOMY, 2021)
Boichyk I.M., Sobko O.M., Spyak H.I. THE LEVEL AND QUALITY OF TRADE SERVICES: THE ESSENCE AND RELATIONSHIP OF CONCEPTS Purpose. The aim of the article is generalization of theoretical provisions on the nature, level and quality of trade services to consumers, identification of the content relationship between them and the role in meeting market demands of the population. Methodology of research. The following research methods were used to achieve this goal: theoretical analysis, abstract and logical – to reveal the essence of trade services, its level and quality; interpretations and comparisons – to determine the relationship and interaction of the concepts of “level” and “quality” of trade services; graphical – to visualize the classification of indicators for assessing the quality of trade services. Findings. It is established that trade service in modern conditions together with quality of the goods offered to consumers is an element of maintenance of competitive advantages of the trading enterprises. This is due to the growing demands of consumers not only to the consumer characteristics of goods, but also related to their sale of trade services. It is substantiated that the concepts of “level of trade service” and “quality of trade service” are not identical concepts. The first of them reflects a set of elements of providing consumers with a variety of services to create a comfortable environment for the purchase of goods and reflects the situation “present or absent” a specific element of trade services. The second is the degree of compliance of the level of trade service with the expectations and needs of consumers, which can be quantified. Originality. The substantiation of the essence, content and correlation of the concepts “the level of trade service” and “quality of trade service”, their influence on the competitiveness of trade enterprises was further developed. Practical value. Substantiated research results can be used by commercial enterprises to assess the effectiveness of their activities in terms of ensuring a higher level and quality of trade services on the basis of these elements and indicators. Key words: trade enterprise, trade service, level of trade service, quality of trade service, competition.